MONETARY ECONOMICS: POLICY AND ITS THEORETICAL BASIS - Bain Keith; Howells Peter (Palgrave Macmillan, 2003)
THE MEANING OF MONEY DEFINITIONS OF MONEY IN ECONOMICS THE MONEY SUPPLY PROCESS MONEY SUPPLY AND CONTROL IN THE UK THE THEORY AND DEMAND FOR MONEY TESTING THE DEMAND FOR MONEY FUNCTION
THE MEANING OF MONEY DEFINITIONS OF MONEY IN ECONOMICS THE MONEY SUPPLY PROCESS MONEY SUPPLY AND CONTROL IN THE UK THE THEORY AND DEMAND FOR MONEY TESTING THE DEMAND FOR MONEY FUNCTION